2013
DOI: 10.1371/journal.pone.0068316
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Withdrawal and Susceptibility to Cardiac Arrhythmias in Rats with High Trait Aggressiveness

Abstract: Personality characteristics, e.g. aggressiveness, have long been associated with an increased risk of cardiac disease. However, the underlying mechanisms remain unclear. In this study we used a rodent model for characterizing cardiac autonomic modulation in rats that differ widely in their level of aggressive behavior. To reach this goal, high-aggressive (HA, n = 10) and non-aggressive (NA, n = 10) rats were selected from a population (n = 121) of adult male Wild-type Groningen rats on the basis of their laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 44 publications
9
40
0
Order By: Relevance
“…The findings of increased aggressive behaviours in depressed mice are consistent with previous reports examining the effects of stress on aggression in adult rodents, primates and human (Carnevali et al 2013;Crombach and Elbert 2014;Howell et al 2013). The tube test may reveal significant differences in mice with altered motor function or impulsivity, or under conditions of social stress (Kalueff et al 2007), and was originally developed as a test of social hierarchy/dominance.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of increased aggressive behaviours in depressed mice are consistent with previous reports examining the effects of stress on aggression in adult rodents, primates and human (Carnevali et al 2013;Crombach and Elbert 2014;Howell et al 2013). The tube test may reveal significant differences in mice with altered motor function or impulsivity, or under conditions of social stress (Kalueff et al 2007), and was originally developed as a test of social hierarchy/dominance.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, a number of publications showed that HRV analysis works well in discriminating among different acute and chronic, environmental and social challenges, between aggressive and nonaggressive individuals, as well as in anxiety studies or studies on mutant mice (Carnevali et al, 2012a(Carnevali et al, , 2013(Carnevali et al, , 2014aCostoli et al, 2004Costoli et al, , 2005Sgoifo et al, 1997Sgoifo et al, , 2005.…”
Section: Animal Models Of Depression and Autonomic Imbalancementioning
confidence: 99%
“…Furthermore, when coping style was determined prior to chronic intermittent stress there was an association between passive coping and hypertension (Hawley et al, 2010). Alternatively, the cardiovascular responsivity of rats exhibiting either high or low aggression is also distinctly different; with high aggression rats displaying reduced vagal antagonism and increased tachyarrhythmias compared with non-aggressive rats (Carnevali et al, 2013a) Taken together, these studies indicate that the behavioral coping response is associated with cardiovascular susceptibility to stress.…”
Section: Role Of the Lc In Individual Differences In Cardiovascular Rmentioning
confidence: 99%